KAJIAN ETNOBOTANI TUMBUHAN JALUKAP (Centella asiatica L.) DI SUKU DAYAK BUKIT DESA HARATAI 1 LOKSADO - Dharmono Dharmono (Universitas Lambung Mangkurat, 2007)
Dayak Bukit community in Loksado has a long history of usage of various kinds of plants in their daily living, either as food, medicine, or in rituals. In the present study ethnobotanic investigations were performed on jalukap plant (Centella asiatica L) to document the use of the plant by people of Loksado. Botanical study revealed that the plant has simpodial branching, single foliation, indefinite composite inflorescence, composite fruit, and fibrous root. Ethnopharmacological study documented the use of the plant for fish poisoning, as well as for wound and bleeding cough medication. Ethnoanthropologically people use the plant in a ritual against flood disaster. Ethnoeconomic study revealed low economic value of the plant as Loksado people use it only within the community. Ethnolinguistic study documented that the name ‘jalukap’ originated from the form of the leaves which resembles human palm; in Banjarese the word ‘jalukap’ means palm.